Konseling Pasutri dalam Perspektif Pastoral dan Biblika: Suatu Analisis Teologis-Implikatif bagi Pembinaan Keluarga Kristen di Era Modern - Harni Lando; Hosanna Anche Pepayoza Br. Bangun (JUITAK: Jurnal Ilmiah Teologi dan Pendidikan Kristen, 2025)
The cultural transformation resulting from secularization, digitalization, and a crisis of values in the modern era has posed serious challenges to the resilience of Christian marriages. The relationship between husband and wife is threatened not only by external issues but also by a lack of deep understanding of marital spirituality in the light of Christian faith. This study aims to examine marital counseling from pastoral and biblical perspectives as a theologically integrative approach to Christian family formation. The focus of the study is directed toward identifying the absence of a counseling model grounded in contextual theology and rooted in biblical foundations. The methodology employed is a literature review with a critical analysis of pastoral theology sources, biblical studies, and contemporary counseling practices published between 2015 and 2025. The findings reveal that marital counseling, when grounded in pastoral and biblical frameworks, serves not only as a means of conflict resolution but also as a channel for reconciliation, faith development, and relational restoration based on God's grace. The novelty of this study lies in its formulation of a marital counseling approach that contextually integrates transformative pastoral principles and biblical theological narratives. Theoretically, this research expands the horizon of pastoral family theology in the digital-modern context, while practically, it provides a pastoral framework for churches to facilitate the restoration and formation of Christian households. Thus, pastoral-biblical-based marital counseling can play a strategic role in building a resilient and theocentric marital spirituality.